2005
DOI: 10.1111/j.1365-2648.2005.03584.x
|View full text |Cite
|
Sign up to set email alerts
|

Swedish women's satisfaction with medical and emotional aspects of antenatal care

Abstract: Midwives working in antenatal care should support pregnant women and their partners in a professional and friendly way in order to increase satisfaction with care. Organizing teamwork with no more than two midwives taking care of a woman during a normal pregnancy could make women feel more supported by their midwives.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

9
65
3
4

Year Published

2008
2008
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 90 publications
(81 citation statements)
references
References 36 publications
9
65
3
4
Order By: Relevance
“…Evidence from this study suggests that the highest rate for mothers' satisfaction with delivery by cesarean was reported by 100% of the respondents in public hospitals and 96.2% in private ones. Some studies confirm our point (15,16). This high level of satisfaction in our study might result from the ignorance of mothers about patient rights.…”
Section: Discussionsupporting
confidence: 73%
See 1 more Smart Citation
“…Evidence from this study suggests that the highest rate for mothers' satisfaction with delivery by cesarean was reported by 100% of the respondents in public hospitals and 96.2% in private ones. Some studies confirm our point (15,16). This high level of satisfaction in our study might result from the ignorance of mothers about patient rights.…”
Section: Discussionsupporting
confidence: 73%
“…Nurses should talk as gently as possible. Our findings revealed emotional satisfaction during labor was lower than post-operative stage in both kind of hospitals (14,16). In Simbar et al study the lowest level of satisfaction was about emotional aspect of satisfaction during labor phase at university teaching hospitals (4).…”
Section: Discussionmentioning
confidence: 81%
“…This result was attributed to shortage of health care providers, in the studied settings. (33) On the other hand, This finding is different than the findings of Hildingsson I et al (2005) (34) and Hansen P et al (2008). (35) They all had revealed that the majority of their subjects were satisfied with their received physical care.…”
Section: Discussionmentioning
confidence: 84%
“…Today, fathers are encouraged to participate in antenatal care, including the ultrasound examination, because this examination is described as being part of the process of becoming a parent (Ekelin, Crang-Svalenius, & Dykes, 2004). Despite fathers' extended involvement in antenatal care, both parents report that fathers are often given a secondary role during childbirth education and antenatal care (Hildingsson & Rådestad, 2005;Premberg & Lundgren, 2006). Fathers have also experienced hospital policies that exclude them from postpartum care and do not encourage them to become involved with their baby (de Montigny & Lacharite, 2004).…”
Section: Introductionmentioning
confidence: 99%